Dinâmica do fitoplâncton e condicionantes limnológicos nas escalas de tempo (nictemeral/sazonal) e de espaço (horizontal/vertical) no açude Traperoá II: trópico semi-árido nordestino - Barbosa, José Etham de Lucena (2002)
In the semi-arid North-east region of Brazil occurs the second highest density of dams in the world (or açudes , as they are locally known) which supply water to ca. 40 millions inhabitants, mainly during the dry period, a catastrophic and frequent event in that Brazilian region. The limnological functioning of such water system in the Taperoá II dam (07o11 44 S and 07o13 44 S, 36o52 03 W and 36o50 09 W) was investigated through sampling carried out between September/1998 and September/2000. Sampling was performed at four collecting stations: three of them at the pond margins and one in its pelagic zone, where four depths were selected: surface, 50% and 1% light penetration, and at 4.0m depth. Climatological characteristics of the region (air temperature, evaporation, winds, and rainfall) were analysed, as well as the physical and chemical properties of the water (temperature, dissolved oxygen, pH, electric conductivity, alkalinity, turbidity, transparency, total dissolved inorganic carbon, ammonia, nitrite, nitrate, total phosphorus, orthophosphate, and silicate). Climatic variations due to El Niño event (1997-1998) caused, between September/98 and January/99, a drastic reduction of the available stock of water in the pond, which determined a strong concentration of dissolved salts, an alkaline pH, high electric conductivity and high inorganic nutrient contents. The diluter effect of the increased rainfall in February and March/1999 exerted a reduction of oxygen, conductivity, and dissolved nutrients and caused water acidity. The recovery of the pond hydrometric volume and its stability, maintained the limnological variables almost unchanged up to the next rainy period. A relative thermal stratification occurred between February and April/2000 simultaneously to a chemical stratification. The Principal Components analysis allowed to distinguish the system based on the highest limnological variables here studied and the water volume fluctuation, showing that the interaction of extreme dry season and rainfall in a short period, are the strongest determinants of the high interannual variability of the sampled variables and of the reduced spatial oscillations of the horizontal and vertical axes of the dam.